Evaluation of the Logan & Boyce plaque index for the study of dental plaque accumulation in dogs - Hennet, Philippe; Servet, Eric; Salesse, Hélène; Soulard, Yannick (Research in veterinary science, 2006)
The objectives of this study were to assess intra-examiner (experienced examiner) and inter-examiner agreements (experienced versus non-experienced examiners) of scores assessed with the Logan & Boyce plaque index and to evaluate whether a modification of this index, where anatomical landmarks are used for horizontal division [mod L&B-AL] and dye references are used for assessing intensity of dye (plaque thickness) [mod L&B-DR], would improve repeatability. The Logan & Boyce index was found to be inaccurate when scoring plaque coverage as it underestimated the total crown surface. The contribution of the gingival part to the total tooth score was minimized by the Logan & Boyce index compared to the mod L&B-AL/DR. Precision of global plaque scorings was significantly improved by the mod L&B-AL/DR. Intra-examiner agreement of plaque thickness and plaque coverage scorings on the gingival part of the tooth was significantly improved by the mod L&B-AL/DR. Studies evaluating plaque accumulation in dogs should therefore use the mod L&B-AL/DR rather than the Logan & Boyce index.